2021
DOI: 10.21608/jpp.2021.157373
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effect of Different Mineral Nitrogen Fertilizer Sources on Productivity and Quality of Some Egyptian Cotton Cultivars

Abstract: Developing cotton cultivars with a high yielding potential, nutrients extract and efficient, fiber attributes, earliness, high oil as well as protein cottonseed contents and pest resistance across variable environments is of great importance of cotton breeding programmer in Egypt. The field experiments were carried out at Agric. Res. and Exp. Stat., Fac. Agric., Cairo Univ., Giza, Egypt during 2017 season and repeated in 2018 season to evaluate the productivity and fiber technology response of three new releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In addition to, the plant height and leaf area, as well as the straw yield which affected by the number of plants and plant height during the growing season. Hossain et al (2006), El-Sayed andHammad (2007) and El-Hag (2008) reported that, increasing nitrogen fertilizer led to increase number of spikes /m 2 , number of grains/spike and grain yield. Salem (2005), Alam et al (2007), Gul et al (2012), Iqbal et al (2012), Gomaa et al (2015) Ullah et al (2018) and Araya et al (2019) found that increasing nitrogen rates resulted in a progressive increase for all the studied traits.…”
Section: -Mean Performancementioning
confidence: 99%
“…In addition to, the plant height and leaf area, as well as the straw yield which affected by the number of plants and plant height during the growing season. Hossain et al (2006), El-Sayed andHammad (2007) and El-Hag (2008) reported that, increasing nitrogen fertilizer led to increase number of spikes /m 2 , number of grains/spike and grain yield. Salem (2005), Alam et al (2007), Gul et al (2012), Iqbal et al (2012), Gomaa et al (2015) Ullah et al (2018) and Araya et al (2019) found that increasing nitrogen rates resulted in a progressive increase for all the studied traits.…”
Section: -Mean Performancementioning
confidence: 99%